Enhanced electrochemiluminescence of N-(aminobutyl)-N-(ethylisoluminol) functionalized gold nanoparticles by Graphene Oxide Nanoribbons - Ismail, Nur Syakimah; Le, Quynh Hoa; Hasan, Quamrul; Yoshikawa, Hiroyuki; Saito, Masato; Tamiya, Eiichi (Elsevier Ltd., 2015)
The mechanism of electrochemiluminescence (ECL) of an N-(aminobutyl)-N-(ethylisoluminol) -functionalized gold nanoparticle (ABEI-AuNP) hybrid with graphene oxide nanoribbons (GONRs) as a functional supporting matrix on a modified screen-printed electrode (SPE) was studied under alkaline conditions.In our catalytic system, ABEI-AuNPs supported by GONRs were profoundly superior to the unsupported ABEI-AuNP/SPE, and exhibited greatly enhanced ECL intensity (≈30.0%).This difference is attributed not only to an 80.2% increase in the total surface area of the ABEI-AuNP-GONR/SPE, but also to enhancements of the ABEI-AuNP catalytic activity resulting from metal-oxygen bonding between the functional groups on the GONRs and the Au active sites.This improved catalytic activity of ABEI-AuNP facilitates both oxidative radical generation and fast reaction kinetics of the ABEI oxidation process. To further elucidate the mechanism of the counter-peak phenomenon in the ABEI ECL under cyclic voltammetry (CV) conditions, the effects of various factors, including pH of buffer solution, existence of dissolved oxygen, and concentration of hydrogen peroxide, on the ECL of ABEI were investigated.The mechanisms of liquid-phase ABEI on bare SPE and GONR/SPE were also compared to that of solid-phase ABEI-AuNP to validate the proposed mechanism for ABEI-AuNP-GONR/SPE.